L'adaptation à la turbulence : les Etats-Unis face aux transformations de I'OTAN, 1989-1991 - Le Prestre, Philippe (Études internationales, 1992)
The end of the Cold War has freed Eastern Europe from the Soviet Union and Western Europe from the United States. This article explores how the Americans have attempted to adapt to these new uncertainties by redefining the threat and by seeking a new political and military identity for NATO. The individual, societal, and external variables that may explain how strategies of adaptation are chosen are then identified. The turbulence of the System, by concentrating decision-making, by giving more weight to budgetary variables, by encouraging neo-isolationist trends, and by favouring local political priorities accentuates an approach of reacting to events and preserving the status quo, an approach which leaves NATO at the mercy of German objectives in Europe without resolving the issue of European security.